The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1073/pnas.87.14.5538
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heads have a broad orientational distribution during isometric muscle contraction: time-resolved EPR studies using caged ATP.

Abstract: To study the orientation of spin-labeled myosin heads in the first few seconds after the production of saturating ATP, we have used a laser flash to photolyze caged ATP during EPR data acquisition. Rabbit psoas muscle fibers were labeled with maleinide spin label, modifying 60% of the myosin heads without impairing muscle fiber biochemical and physiological activity (ATPase and force). The muscle bundles were incubated for 30 min with 5 mM caged ATP prior to the UV flash. The flash, from an excimer laser, libe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
61
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 26 publications
13
61
2
Order By: Relevance
“…However, other in vitro studies reported an angle close to that in rigor (Zot et al, 1990). The EPR studies that showed rotational motion of heads during contraction (Cooke et al, 1982;Barnett & Thomas, 1989;Fajer et al, 1990) are also consistent with our results.…”
Section: Angles Of the Crossbridgessupporting
confidence: 82%
See 1 more Smart Citation
“…However, other in vitro studies reported an angle close to that in rigor (Zot et al, 1990). The EPR studies that showed rotational motion of heads during contraction (Cooke et al, 1982;Barnett & Thomas, 1989;Fajer et al, 1990) are also consistent with our results.…”
Section: Angles Of the Crossbridgessupporting
confidence: 82%
“…X-ray diffraction (Huxley & Brown, 1967;Yagi et al, 1981;Huxley et al, 1982) and EPR studies (Cooke et al, 1982;Barnett & Thomas, 1989;Fajer et al, 1990) have suggested that the averaged structure of contracting muscle is different from that of rigor or relaxed muscle. The results of X-ray diffraction were interpreted to mean that during contraction the helical arrangement of myosin heads along thick filaments is disordered but the --, 14.3 nm subunit repeat is maintained.…”
Section: -4319 © 1993 Chapman and Hallmentioning
confidence: 99%
“…(4, 5559) In the S state, myosin heads form stereospecific contacts with actin, while in the W state the catalytic and light-chain domains of the myosin head show rotational disorder on the microsecond time scale. (4, 24, 55, 58, 6064) TPA studies with probes on actin have shown that actin also has two predominant structural states, S and W (more dynamically disordered), related to the structural states of the interacting myosin head. (2, 6, 7)…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that the S 1-induced changes in the above studies do not reflect conformational changes in actin but reflect local rotations ofthe probes or their immediate environments (Fajer et al, 1990b). To investigate these possibilities more thoroughly, (a) spin labels should be attached to other sites on actin (e.g., the myosin binding site) or (b) caged ATP studies (Ostap and Thomas, 1991;Fajer et al, 1990c) should be done on oriented actin samples.…”
Section: Relationship To Other Workmentioning
confidence: 99%